Qur’an Reading Methods in Post-Soeharto Indonesia: The Conservative Turn, Commodified Piety, and the Reconfiguration of Qur’anic Authority - Mubaidi Sulaeman; Kemas M. Intizham; Abd. Halim; Shinta Nurani (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2026)
Existing studies on Qur’an reading methods in Indonesia have largely examined individual pedagogical models—such as Iqra’, Ummi, Yanbu’a, or Baghdadiyah—while paying limited attention to the political-economic forces shaping their emergence, circulation, and legitimacy in the post-Soeharto era. This article addresses that gap by analyzing Qur’an reading methods not merely as instructional tools but as products embedded within shifting configurations of power, market competition, and religious authority. Using a qualitative library-based approach, the study engages historical scholarship, policy documents, institutional publications, and contemporary literature on Islamic education and religious capitalism. Drawing on Pierre Bourdieu’s theory of field and capital and Talal Asad’s concept of Islam as a discursive tradition, the article demonstrates that Qur’an reading methods function simultaneously as modes of religious transmission, arenas of symbolic and economic competition, and mechanisms for forming pious subjects. The findings show that commodification does not erode religious normativity but rearticulates Qur’anic authority through standardization, certification, branding, and digital mediation. Positioned as a critical test case, Indonesia reveals how Qur’anic education becomes a dynamic site of negotiation between spirituality, authority, and market logic.